PRIMARY SHOULDER-JOINT ARTHROPLASTY IN PATIENTS WITH SEVERE INJURIES OF PROXIMAL HUMERUS - M. O. Radzhabov; M. M. Alexanyan; V. M. Kochemasov; I. N. Nikolsky (Неотложная медицинская помощь, 2017)
Introduction. Lesions of proximal humerus occur often nowadays. Many surgical methods are performed in such situations.Material and Methods. In October 2014 — August 2016, 25 patients with severe lesions of proximal humerus underwent primary unipolar shoulder joint arthroplasty in the Trauma Department no. 2 of S. Yudin City Clinical Hospital. AO\ASIF classification was used. The results were evaluated in the period from 5 to 18 months by Swanson shoulder score. The result 20-30 points was assessed as excellent, 10–19 points — fair, less than 10 points — poor.Objectives. To evaluate immediate and midterm results of the unipolar shoulder joint arthroplasty in severe injuries of the proximal humerus.Results. Good results were received in 19 cases (76%), fair results were achieved in 6 (24%) cases and there were no poor results. There were no intraoperative or postoperative complications.Discussion. It is preferable to perform hemiarthroplasty if glenoid surface is intact. In such cases the results are similar to total arthroplasty. Standard surgical technics were used in all patients. All of them underwent rehabilitation courses after the surgery and returned to daily life and work.Conclusion: Primary shoulder joint arthroplasty may be considered as a method of choice for severe fractures and fractures with dislocation of head and surgical neck of humerus.